LITERASI MEDIA SOSIAL UNTUK REMAJA KATOLIK PAROKI MALAIKAT AGUNG GABRIEL BATAM - Suharyanto, Cosmas Eko (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2023)
The Indonesia's digital literacy status is still not good. Even though Indonesia's digital literacy status in 2022 was recorded to have increased by 0.5 from the previous year, namely 3.49 to 3.54, this score shows that national digital literacy is still in the medium category. Through a social media literacy workshop for youth at Archangel Gabriel Tembesi Parish, we wants to contribute to focus on digital skill indicators. From the results of the dedication, youth are able to produce good content, as well as being able to distinguish positive and negative information.